KEPATUHAN TERHADAP PRINSIP PEMBAYARAN MENGGUNAKAN MEKANISME UANG PERSEDIAAN PADA APLIKASI SAKTI - Trisulo, Trisulo; Susilo, Budi (Ilmu Hukum Prima (IHP), 2024)
This research aims to analyze the implementation of spending using the SAKTI application in government work units based on the Regulation of the Minister of Finance of the Republic of Indonesia Number 210/PMK.05/2022 concerning Payment Procedures in the Context of Implementing the State Revenue and Expenditure Budget. This research is normative juridical, using statute and conceptual approaches, written descriptively analytically. The study analyzes the payment procedures for goods purchases by government work units in the treasurer module of the SAKTI application. The research results generally show that government work units have experienced the benefits of SAKTI in terms of administration and payment of government work units according to the mechanisms/procedures established by applicable regulations. Various interpretations of payment techniques using the SAKTI application have resulted in additional procedures carried out by government work units that are not regulated and even conflict with the Regulation of the Minister of Finance of the Republic of Indonesia Number 210/PMK.05/2022.  Additional procedures that conflict with regulations need to be evaluated and refined in the SAKTI application so that it complies with generally applicable legal provisions and principles.